Antropologia, religione, diritto - Cardia, Carlo (Omosessualità e matrimonio nei diritti delle religioni e degli stati, 2015)
Great religions have fostered the evolution of humanity, which in turn has helped to purify them. The development of the original anthropological religious conceptions evolves, especially in a Christian environment, through the recognition of the dualism between law and religion in civil law, and loosens its ties with temporal powers, of which it has been sometimes historical accomplice. Human rights are, then, a valid horizon for all, but recently they opened the doors to ethical-legal relativism that changes the sense of secularism, assimilates ethics and religion, and proclaims the dominance of the ego. This is the beginning of the end of human rights. Beginning from the topics of sexuality, family, behavioural ethics, a new polytheism takes shape.